Management of wild and cultured sea bass / Barramundi (lates calcarifer) : (Canberra publishing, 1986)
Lates calcarifer, known as sea bass or barramundi, occurs widely and ia prized eating fish in the Indo-Pacific region, but interest in detailed studies of its biology has only arisen recently. At this workshop, scientists involved in L. calcarifer research established priorities or development of fisheries of cultured or wild bass. The publication reviews existing knowledge of: current research in Asia and Australia; management of wild stocks; spawning and rearing in culture; and diseases of wild and cultured populations.